Potent Bioactive Compounds From Seaweed Waste to Combat Cancer Through Bioinformatics Investigation - Bharadwaj, Kaushik Kumar; Ahmad, Iqrar; Pati, Siddhartha; Ghosh, Arabinda; Sarkar, Tanmay; Rabha, Bijuli; Patel, Harun; Baishya, Debabrat; Edinur, Hisham Atan; Abdul Kari, Zulhisyam; Ahmad Mohd Zain, Muhammad Rajaei; Wan Rosli, Wan Ishak (Frontiers in Nutrition, 2022)
The seaweed industries generate considerable amounts of waste that must be appropriately managed. This biomass from marine waste is a rich source of high-value bioactive compounds. Thus, this waste can be adequately utilized by recovering the compounds for therapeutic purposes. Histone deacetylases (HDACs) are key epigenetic regulators established as one of the most promising targets for cancer chemotherapy. In the present study, our objective is to find HDAC 2 inhibitor. We performed top-down in silico methodologies to identify potential HDAC 2 inhibitor by screening compounds from edible seaweeds waste. One hundred ninety-three (n=193) compounds from edible seaweeds were initially screened and filtered with drug-likeness properties using SwissADME. After that, the filtered compounds were followed to further evaluate their binding potential with HDAC 2 protein by using Glide high throughput virtual screening (HTVS), standard precision (SP), extra precision (XP), and Quantum Polarized Ligand Docking (QPLD). One compound with higher negative binding energy was selected, and to validate the binding mode and stability of the complex, molecular dynamics (MD) simulations using Desmond were performed. The complex binding free energy calculation was performed using molecular mechanics-generalized born surface area (MM-GBSA) calculation. Post-MD simulation analyses such as PCA, DCCM, and free energy landscape were also evaluated. The quantum mechanical and electronic properties of the potential bioactive compound were assessed using the Density functional theory (DFT) study. These findings support the use of marine resources like edible seaweed waste for cancer drug development by using its bioactive compounds. The obtained results encourage further in vitro and in vivo research. Our in-silico findings show that the compound has a high binding affinity for the catalytic site of the HDAC 2 protein and has drug-likeness properties, and can be utilized in drug development against cancer.